Anne Frank's family : the extraordinary story of where she came from based on more than 6,000 newly discovered letters, documents, and photos - Pressler, Mirjam 1940-2019 (Anchor Books, 2012)
Traces the discovery by Frank's aunt's daughter-in-law of numerous family correspondences and keepsakes and what they revealed about the Frank family and the forces that shaped the famous young diarist.